Formation and evolution of shear bands in cold rolled Zr40Ti60 alloy. (October 2014) - Wang, X. Y.; Jing, R.; Liu, C. Y.; Zhang, B.; Ma1, M. Z.; Liu, R. P.
<x content-type="archive" xml:space="preserve">Abstract</x> The microstructure evolution and formation of shear bands in Zr40Ti60 alloy during different cold rolling processes were studied in this article. Results indicate that the width of the shear band formed in the sample increases rapidly with the increasing of the thickness reduction of the sample, and the temperature rise caused by plastic deformation played an important role in the evolution process of the shear band. The microstructure within the shear bands much finer than that in the surrounding matrix has been confirmed, and nanosized subgrains were observed at the centre of the shear band with a width of 15 μm. Hardness tests showed that the microhardness within the shear band with a width of 15 μm (537 HV) was markedly higher than that in the surrounding matrix (410 HV).